Anti-Inflammatory, Anti-Hyperglycemic, and Anti-Aging Activities of Aqueous and Methanolic Fractions Obtained from Cucurbita ficifolia Bouché Fruit Pulp and Peel Extracts - Tiago E. Coutinho; Carlos Martins-Gomes; Liliana Machado-Carvalho; Fernando M. Nunes; Amélia M. Silva (Molecules)
The Cucurbita genus comprises various species that are globally consumed and that are commonly used for their nutritional value but also for medicinal applications. Within the Cucurbita genus can be found Cucurbita ficifolia Bouché, a species that is understudied regarding its potential value for the food industry, as a functional food, and for the pharmaceutical industry, as a source of nutraceuticals. Therefore, in this study we investigated the phytochemical composition and bioactivities of aqueous (AF) and methanolic (MF) fractions of C. ficifolia pulp and peel hydroethanolic (HE) extracts. HPLC-DAD-MSn and HPAEC-PAD analyses of extracts’ fractions revealed a low content of polyphenols and a significant content of sugars. Through in vitro inhibition assays of the enzymes alpha-amylase, acetylcholinesterase (AChE), and elastase, all fractions showed, respectively, antidiabetic, neuroprotective, and anti-aging activities. The safety profile and anti-tumoral activities were evaluated in various cell models (Caco-2, HaCaT, HepG2, and RAW 264.7), and results showed that the fractions obtained from pulp extract induce no/low cytotoxicity, while the methanolic fraction of peel induced cytotoxicity in all cell lines. At non-cytotoxic concentrations, aqueous and methanolic fractions of both extracts significantly inhibited nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells, revealing anti-inflammatory activity. Flow cytometry analysis showed that both aqueous fractions increased basal levels of glutathione (GSH) in Caco-2 cells, while not inducing oxidative stress, revealing potential as antioxidant dietary agents. However, the MF of peel HE extract induced oxidative stress in Caco-2 cells, as it increased reactive oxygen species (ROS) and lipid peroxidation. AF fraction of peel extract induced cell cycle arrest in the G0/G1 phase, while the other fractions induced cell cycle arrest in the S phase. In conclusion, Cucurbita ficifolia fruit presents potential as a functional food but also as a potential source of nutraceuticals, and peel waste products can be valorized by pharmaceutical and cosmeceutical industries as sources of bioactive molecules.